Fundamentals of O-RAN - Tripathi, Nishith D.; Shah, Vijay K. (Wiley, 2025)
Comprehensive reference on O-RAN technology, covering its history, architecture, security, ecosystem, and more, with didactic resources included throughout Discussing both basic and advanced concepts, Fundamentals of O-RAN delivers a comprehensive summary of O-RAN, covering its history, architecture, control loops and microservices (i.e., xApps and rApps), security, ecosystem, R&D initiatives, and challenges and evolution toward 6G. The book not only includes key theoretical principles of O-RAN, but also provides a framework for the reader to carry out guided hands-on exercises through online auxiliary materials. Homework problems and review questions are included in online auxiliary materials to reinforce learning.
Keywords: Elektronik, Elektrotechnik, Nachrichtentechnik